2022
DOI: 10.3390/ijerph19095142
|View full text |Cite
|
Sign up to set email alerts
|

Using Structural Equation Modeling to Examine Pathways between Physical Activity and Sleep Quality among Chinese TikTok Users

Abstract: TikTok, the most popular social media, brings various benefits to nowadays living. However, the problematic use of TikTok has also elicited a range of health problems, such as sleep problems. Physical activity (PA) appears to play a protective role in the problematic use of TikTok and its health consequences, but the pathways between PA and sleep health are understudied. Therefore, we aimed to propose a framework to check whether PA can benefit the sleep health of TikTok users by reducing bedtime delays for Ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 86 publications
2
12
0
Order By: Relevance
“…Zhang et al suggested that the most medical information on TikTok were low-quality content and could be easily accessible. 15 In our study, the “good” (38.9%) and “excellent” (3.2%) DISCERN classification account for a small portion of all searched results. In our research, the mean DISCERN values of included results was 43.8, with an average JAMA scores of 2.7, indicating a relatively intermediate quality and reliability.…”
Section: Discussionmentioning
confidence: 52%
“…Zhang et al suggested that the most medical information on TikTok were low-quality content and could be easily accessible. 15 In our study, the “good” (38.9%) and “excellent” (3.2%) DISCERN classification account for a small portion of all searched results. In our research, the mean DISCERN values of included results was 43.8, with an average JAMA scores of 2.7, indicating a relatively intermediate quality and reliability.…”
Section: Discussionmentioning
confidence: 52%
“…Video-sharing platforms, including Tiktok, Bilibili, and Weibo, have become increasingly popular and essential channels for health information dissemination for Chinese people, with user-friendly experiences on computers and smart mobile phones [26]. As one of the most popular video-sharing platforms in mainland China, TikTok Chinese web version, has more than 500 million daily users in China [27]. In 2022, more than 35000 certi ed doctors uploaded about 4.43 million popular science videos on TikTok [28].…”
Section: Discussionmentioning
confidence: 99%
“…As far as we know, there are few studies concerning the relationship between PA and bedtime smartphone-related issues. Our previous study found that PA was negatively associated with sleep delay for TikTok use [ 33 ]. In the current study, we focused on smartphone-related sleep delay and limited PA to the daytime scenario and observed a similar result.…”
Section: Discussionmentioning
confidence: 99%
“…However, the causal relationship between the two variables cannot be confirmed due to the cross-sectional design [ 49 ]. Some scholars have assumed smartphone use limits PA and vice versa [ 33 , 50 ]. The presented study is also based on a cross-sectional investigation, but the investigated variables have a time sequence.…”
Section: Discussionmentioning
confidence: 99%